MODERN TRENDS IN TEACHING FOREIGN LANGUAGES AND INTERCULTURAL COMMUNICATION (ON THE EXAMPLE OF GERMAN) - Kurbonova Nargiza Samadovna; Eshmirzayeva Madina Rustam qizi (Scholars Digest Publishing, 2023)
The methods of teaching German today may not be exactly the same as 10-15 years ago. First of all, because in the era of the Internet and desktop systems, a lot of opportunities for teaching German appear before the teacher. Among them are interactive courses, online communication, watching films in German and many others, the use of which in the classroom depends on the teacher's personal creative approach. This article provides a theoretical approach to the methods and effective ways of teaching a foreign language.
Keywords: the cognitive sphere of the subject, the motivational sphere of the individual, linguistic consciousness, the modern approach to teaching, the pedagogical experience shows.